DESAIN PEMBELAJARAN MODEL ASSURE UNTUK MATA KULIAH BAHASA INGGRIS DI UNIVERSITAS - Zaldi Harfal; Novitri Novitri; Mirza Hardian (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2022)
Instructional design has a strong influence on the success of university-level learning. Learning in higher education is effective if it is designed properly by the course unit tutor because the instructional design helps the preparation of a good lesson plan that contains objectives, materials, methods, media, class activities, evaluations, and so on. There are various instructional design models and one of the popular designs for media application is ASSURE. Some experts use the acronym ASSURE differently. In this article, ASSURE consists of Analyze learners, State objectives, Select method-media-materials, Utilize media-materials, Require learner participation, Evaluate and revise. The ASSURE model can be applied to various fields of study and levels, but has never been published in English language learning at university. Therefore, this article will explain the application of the ASSURE model in general English courses in universities.